Mechanism of trans-translation revealed by in vitro studies - Himeno, Hyouta; Kurita, Daisuke; Muto, Akira (Frontiers in Microbiology, 2014)
tmRNA is a bacterial small RNA having a structure resembling the upper half of tRNA and its 3’ end accepts alanine followed by binding to EF-Tu like tRNA. Instead of lacking a lower half of the cloverleaf structure including the anticodon, tmRNA has a short coding sequence for tag-peptide that serves as a target of cellular proteases. An elaborate coordination of two functions as tRNA and mRNA facilitates an irregular translation termed trans-translation: a single polypeptide is synthesized from two mRNA molecules. It allows resumption of translation stalled on a truncated mRNA, producing a chimeric polypeptide comprising the C-terminally truncated polypeptide derived from truncated mRNA and the C-terminal tag-peptide encoded by tmRNA. Trans-translation promotes recycling of the stalled ribosomes in the cell, and the resulting C-terminally tagged polypeptide is preferentially degraded by cellular proteases. Biochemical studies using in vitro trans-translation systems together with structural studies have unveiled the molecular mechanism of trans-translation, during which the upper and lower halves of tRNA are mimicked by the tRNA-like structure of tmRNA and a tmRNA-sepecific binding protein called SmpB, respectively. They mimic not only the tRNA structure but also its behavior perhaps at every step of the trans-translation process in the ribosome. Furthermore, the C-terminal tail of SmpB, which is unstructured in solution, occupies the mRNA path in the ribosome to play a crucial role in trans-translation, addressing how tmRNA·SmpB recognizes the ribosome stalled on a truncated mRNA.